2002
DOI: 10.1093/nar/30.3.656
|View full text |Cite
|
Sign up to set email alerts
|

Supercoiling, knotting and replication fork reversal in partially replicated plasmids

Abstract: To study the structure of partially replicated plasmids, we cloned the Escherichia coli polar replication terminator TerE in its active orientation at different locations in the ColE1 vector pBR18. The resulting plasmids, pBR18-TerE@StyI and pBR18-TerE@EcoRI, were analyzed by neutral/neutral two-dimensional agarose gel electrophoresis and electron microscopy. Replication forks stop at the Ter-TUS complex, leading to the accumulation of specific replication intermediates with a mass 1.26 times the mass of non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 47 publications
2
97
0
Order By: Relevance
“…All the immunograms were aligned attending to the mobility of OCs. Note that chloroquine's intercalation has no effect on the electrophoretic mobility of nicked unreplicated molecules (29,37,50).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the immunograms were aligned attending to the mobility of OCs. Note that chloroquine's intercalation has no effect on the electrophoretic mobility of nicked unreplicated molecules (29,37,50).…”
Section: Resultsmentioning
confidence: 99%
“…This intercalation changes DNA twist. As bacterial plasmids are (Ϫ)-supercoiled, chloroquine removes (Ϫ)-supercoiling first and adds net (ϩ)-supercoiling only after all native (Ϫ)-supercoiling has been removed (37,51). Moreover, it was repeatedly shown that in partially replicated molecules containing three-way forks, overwinding of the unreplicated region transforms three-way into four-way junctions called reversed forks or chicken feet (37, 50 -53).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second dimension was in 1% agarose gel in TBE buffer containing increasing concentrations of EthBr run perpendicular with respect to the first dimension. The dissolved agarose was poured around the excised agarose lane from the first dimension, and electrophoresis was at 5 V/cm in a 4°C cold chamber for 10 h. Southern transfer was performed as described (11,21). placed 7 cm above the plastic dish, and the light was filtered through a Pyrex glass to remove radiation Ͻ300 nm.…”
Section: D Agarose Gel Electrophoresis and Southernmentioning
confidence: 99%